DYNAMICS AND FUNCTION OF THE REDOX REGULATORY NETWORK OF PLANTS UNDER STRESS (Proceedings of the YSU B: Chemical and Biological Sciences, 2024)
Environmental changes have profound impacts on biological systems, trig-gering a cascade of enzymatic and chemical reactions, molecular rearrangements, and alterations in molecular interactions. In the face of environmental stressors, plants employ various protective mechanisms to maintain cellular homeostasis. Reactive oxygen species (ROS), generated during metabolic processes, serve as signaling molecules regulating plant metabolic pathways. To counteract the detrimental effects of ROS accumulation, plants possess robust ROS-scavenging mechanisms. These encompass enzymatic antioxidants such as superoxide dismutase, catalase, monodehydroascorbate, peroxiredoxins, alongside non-enzymatic antioxidants like ascorbic acid, α-tocopherols, glutathione, proline, phenolic substances, and carotenoids. However, under stress conditions and toxin exposure, ROS generation escalates within plant cells, particularly in organelles like chloroplasts, peroxisomes, and mitochondria, leading to oxidative stress and cellular damage. Studies employing gas chromatography-mass selective analyses revealed significant concentrations of methyl chavicol and menthol in essential oils extracted from select plant species. In vitro studies utilizing PAM-fluorometric data demonstrated optimal treatment periods for Arabidopsis thaliana leaf disks, aiding in elucidating potential allelochemical action mechanisms. Redox gel electrophoresis coupled with immune analysis facilitated the assessment of the redox status of key proteins in vivo, notably chloroplast peroxiredoxin (2-CysPrx), pivotal in photosynthetic regulation. Investigation into the redox status of 2-CysPrx under essential oil treatments unveiled menthol-induced oxidation and subsequent dimerization of the enzyme, suggesting a disruption in photosynthetic processes. Non-protein thiols (NPT), including glutathione (GSH), play vital roles in plant stress tolerance. Deviations in NPT concentrations serve as indicators of cellular redox status. Notably, treatment with menthol resulted in a statistically significant decrease in NPT levels, corroborating findings of altered peroxiredoxin redox states and implying perturbations in cellular homeostasis. Moreover, NIR KLAS 100 data highlighted allelochemical influences on the photosynthetic apparatus of A. thaliana wild-type and mutant plants, further elucidating the impacts of these compounds on plant physiological processes.
Keywords: Mentha arvensis; Ocimum basilicum var. purpureum; allelopathic activity; peroxiredoxins